THE SOCIAL DISTINCTION IN AGUS NOOR'S KISAH-KISAH KECIL DAN GANJIL MALAM 1001 PANDEMI - Darsita Suparno (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
This article is motivated by social cases written by Agus Noor in reporting story cases during the pandemic. This study aims to find three model social semiotics: 1) field; 2) tenor;3) mode are used to revealed social distinction that occur in the novel Kisah-Kisah Kecil dan Ganjil Malam 1001 Pandemic by Agus Noor. It is addressed to portray the language used that reflects social disctintion as people who are suffering during a pandemic by using Halliday's theory. The research of this study is qualitative. The finding of this study revealed namely (1) 115 story topics about the outbreak that have been divided into eight sections each section consists of 15-17 sub-topics; (2) language signs refer to lexis in the form of words, phrases, and sentences about the pandemic situation, there are 108 fields of discourse, 86 tenor of discourse, and 48 mode of discourse; (3) there are five kind of social distinctions, namely (i) socio-economic status; (ii) wealth; (iii) power; (iv) honor or prestige; (v) education.